GABAB Receptor Antagonist CGP46381 Inhibits Form-Deprivation Myopia Development in Guinea Pigs. (11th January 2015) - Cheng, Zhen-Ying; Wang, Xu-Ping; Schmid, Katrina L.; Han, Yu-Fei; Han, Xu-Guang; Tang, Hong-Wei; Tang, Xin
Abstract : The aim was to investigate the effects of the GABA B receptor antagonist, CGP46381, on form-deprivation myopia (FDM) in guinea pigs. Twenty-four guinea pigs had monocular visual deprivation induced using a diffuser for 11 days (day 14 to 25). The deprived eyes were treated with daily subconjunctival injections (100 μ l) of either 2% CGP46381, 0.2% CGP46381, or saline or received no injection. The fellow eyes were left untreated. Another six animals received no treatment. At the start and end of the treatment period, ocular refractions were measured using retinoscopy and vitreous chamber depth (VCD) and axial length (AL) using A-scan ultrasound. All of the deprived eyes developed relative myopia (treated versus untreated eyes, P < 0.05 ). The amount of myopia was significantly affected by the drug treatment (one-way ANOVA, P < 0.0001 ). The highest dose tested, 2% CGP46381, significantly inhibited myopia development compared to saline (2% CGP46381: −1.08 ± 0.40 D, saline: −4.33 ± 0.67 D, P < 0.01 ). The majority of these effects were due to less AL (2% CGP46381: 0.03 ± 0.01 mm, saline: 0.13 ± 0.02 mm, P < 0.01 ) and VCD (2% CGP46381: 0.02 ± 0.01 mm, saline: 0.08 ± 0.01 mm, P < 0.01 ) elongation. The lower dose tested, 0.2% CGP46381, did not significantly inhibit FDM (P > 0.0 5 ). Subconjunctival injections of CGP46381 inhibit FDM development in guinea pigs in a dose-dependent manner.